2013
DOI: 10.4172/2157-7560.s1-005
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Rotavirus Disease among Health Care Providers and Their Acceptance of Rotavirus Vaccines in South-East, Nigeria

Abstract: Rotavirus is the commonest cause of severe diarrheal disease worldwide, with prevalence as high as 25% in Nigeria. Severe rotavirus disease is vaccine preventable, with potential to prevent 576 deaths per day in Africa, yet 85% of deaths occur in Africa and South-East Asia.Nigeria is yet to adopt the 2009 WHO recommendation of global inclusion of rotavirus vaccine into the national immunization programme. With pre-existing barriers to immunizing Nigerian children; it is relevant to explore the health-care prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Results obtained from health care providers revealed that majority (83.3%) mentioned that there were no adverse effects received on rotavirus vaccine from parents/guardians of children after vaccination sessions. The findings in this study were similar to those [12] in Nigeria, which revealed insignificant side effects of the vaccine. This study has also revealed that majority (83.3%) of health care providers conducted growth monitoring programs at outreach sites in the last week of each month according to plan.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Results obtained from health care providers revealed that majority (83.3%) mentioned that there were no adverse effects received on rotavirus vaccine from parents/guardians of children after vaccination sessions. The findings in this study were similar to those [12] in Nigeria, which revealed insignificant side effects of the vaccine. This study has also revealed that majority (83.3%) of health care providers conducted growth monitoring programs at outreach sites in the last week of each month according to plan.…”
Section: Discussionsupporting
confidence: 89%
“…A study conducted by Gargano [11] from 2009 to 2010 to predict physicians' perception to identify the predictors of administration and attitude toward vaccines which included rotavirus, revealed that only one tenth of Pediatricians had been routinely administering rotavirus vaccines in India. On the contrary, Nnenna's study conducted [12] in Nigeria revealed that health care providers were more likely to recommend their clients to use the vaccine if it was incorporated in the National Programme of Immunization (72.5%) or recommended by Paediatrics Association of Nigeria (70.3%) or the Federal Ministry of Health (69.2%). About 70.3% of respondents stated that they would have their own children vaccinated if provided freely and only 2.2% mentioned that would not.…”
Section: Introductionmentioning
confidence: 98%